Índice de Proliferación Celular con el marcador Ki67 En Cáncer Oral (2020)
Biomarkers, "are cellular, biochemical or molecular alterations that can be objectively measured and evaluated as an indicator of normal biological processes, pathogenic processes or pharmacological responses to a therapeutic intervention. Objective: To determine the rates of cell proliferation in the well, moderately and p oorly differentiated stages of squamous cell cancer of the oral cavity. Materials and Methods: It corresponds to an experimental research, by the Immunofluorescence method, by means of image capture with the AxioCam I Cm1 coupled to the Axio imager Z2 Micr oscope with motorized z focus and obtained with the EC PlanNeofluar 40x/0.75 M27 objective. The Set 49 filter set was used, which detects the excitation at 358 nm and the emission at 463 nm. With the ZEN Digital Imaging program, the images were captured w ith 300 dpi resolution and in TIFF format. Results: The highest differentials in nuclei per parameter analyzed correspond to welldifferentiated (63% in N), poorly differentiated infiltrating (18.8% in S), moderately differentiated (71.9% in SR), poorly d ifferentiated infiltrating (7.3% in SI), well differentiated (10% in LR), moderately differentiated ulcerated and infiltrating (2.2% in LI) and well differentiated ulcerated and infiltrating (19% in I). Conclusions: 3 types of histological grade were deter mined in the sample; welldifferentiated, moderatelydifferentiated and poorly differentiated squamous cell carcinoma; identifying a greater number of nuclei in poorly differentiated squamous cell carcinoma.